Inhibition of Y1 Receptor Promotes Osteogenesis in Bone Marrow Stromal Cells via cAMP/PKA/CREB Pathway - Yu, Wei; Chen, Fan-Cheng; Xu, Wen-Ning; Ding, Sheng-Long; Chen, Peng-Bo; Yang, Lei; Jiang, Sheng-Dan; Pan, Xiao-Yun (Frontiers in Endocrinology, 2020)
Inhibition of neuropeptide Y1 receptor stimulates osteogenesis in vitro and in vivo. However, the underlying mechanisms involved in these effects remain poorly understood. Here we identify the effects of Y1 receptor deficiency on osteogenic differentiation in human bone marrow stromal cells (BMSCs) by using genetic and pharmacological regulation, and to explore the pathways mediating these effects. In BMSCs, inhibition of Y1 receptor stimulates osteogenesis and upregulates the expression levels of the master transcriptional factor RUNX2. Mechanistically, Y1 receptor deficiency increases the levels of intracellular cAMP, which via protein kinase A (PKA) mediated pathways results in activation of phospho-CREB (p-CREB). We find RUNX2 activation induced by Y1 receptor deficiency is reversed by H-89, a PKA inhibitor. These results indicate Y1 receptor deficiency activates PKA-mediated phosphorylation of CREB, leading to activation of RUNX2 and enhances osteogenic differentiation in BMSCs. In conclusion, these data indicate that Y1 receptor deficiency promotes osteogenic differentiation by RUNX2 stimulation through cAMP/PKA/CREB pathway.